Cytotoxic and genotoxic effects of two medicinal species of verbenaceae - Saulo M., Sousa; Silva, Pâmela S. [UNESP]; Campos, José Marcello S.; Viccini, Lyderson F. (My University, 2009)
Lantana camara L. and Lippia alba (Mill.) N. E. Br. are two important species of Verbenaceae family and are commonly used in folk medicine in many countries of Central and Southern America. The aim of this study was to investigate, for the first time, the cytotoxic and genotoxic effects of aqueous extracts from leaves of both species on Lactuca sativa (lettuce) root tip meristem cells using a cytogenetic approach. Seeds of lettuce were separately treated during 72h with different concentrations of L. camara and L. alba aqueous extracts (5, 10, 20 and 30g/L). The percentage of germination, root development and cellular behavior were analyzed and the results showed that the highest concentration of aqueous extracts reduced the mitotic index, the seeds germination and the root development of lettuce. The extracts also induced chromosome aberrations and cellular death in roots cells of L. sativa. The cytogenotoxicity of L. camara and L. alba extracts was comparatively described. © 2009 Taylor & Francis Group, LLC.
Keywords: Cellular death; Chromosome aberrations; Cytogenotoxicity; Lantana camara; Lippia alba; Mitotic index; Mutagenesis